The transition of graduates of the Faculty of Engineering Universitas Negeri Yogyakarta (UNY) into the labor sector - Fitriani, Winda Sari; Sudira, Putu; Indrihapsari, Yuniar; Rizbudiani, Adilla Desy (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to find out about the transition of graduates of the Faculty of Engineering YSU to the world of work. This study used the tracer study method with respondents filling out a tracer study questionnaire of 573 graduates. The results found that as many as 95% of graduates of the Faculty of Engineering YSU continued their work. As many as 42% of graduates are looking for a job after graduation with less than 6 months for graduates to get a job, the number of companies applied for before getting the first job is 9.6 companies, the average number of companies that respond to graduates’ applications is 53.33% of companies, the average number of companies that invite interviews is 27.33% of companies, the type of work of graduates currently working, namely working in the private sector is 47.96%, 83.982% have the suitability of the field of work with the competence of the field of graduate science education, 95.46% have an education level that is in accordance with current job needs, and the average income of graduates is above Rp. 2,000,000.00. Thus, the average graduate of the Faculty of Engineering YSU is absorbed in the field of employment in accordance with the field of graduate science education well